Pelaksanaan Pembelajaran Musik Ansambel Sejenis di Kelas X AKL SMK Negeri 1 Painan - Dion Marcelindo; Syeilendra Syeilendra (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
This study aims to describe the implementation of similar ensemble music learning in class X AKL SMK Negeri 1 Painan. A type of qualitative research with a descriptive approach. The main instrument in this study is the researcher himself who is assisted by supporting instruments such as stationery, paper, and mobile phones used to record and to take audio visual images. Data collection techniques are carried out by means of literature study, observation, interviews and documentation. The description process begins by examining the data carried out by selective selection. Then the data is displayed in descriptive form and composed in a systematic manner and then conclusions are drawn. The results of the study show that the learning of similar ensemble music runs in accordance with the learning objectives, namely students are able to play instruments in groups well. Piano musical instruments are used as a learning medium that plays two regional songs, namely the Kambanglah Bungo song and the Soleram song with a total of 31 students divided into two study groups. The learning outcomes of the students in the two groups were declared complete with scores above KKM 80.